2019
DOI: 10.3390/met9090995
|View full text |Cite
|
Sign up to set email alerts
|

Porous Titanium Surfaces to Control Bacteria Growth: Mechanical Properties and Sulfonated Polyetheretherketone Coatings as Antibiofouling Approaches

Abstract: Here, titanium porous substrates were fabricated by a space holder technique. The relationship between microstructural characteristics (pore equivalent diameter, mean free-path between pores, roughness and contact surface), mechanical properties (Young’s modulus, yield strength and dynamic micro-hardness) and bacterial behavior are discussed. The bacterial strains evaluated are often found on dental implants: Methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa. The colony-forming unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In previous works, authors have already evaluated the bacterial behavior of porous Ti substrates with different proportions and sizes of pores [4], revealing a greater bacterial adhesion and proliferation in those samples with bigger pore size distribution. Similarly, they investigated a novel methodology to confer antimicrobial character to these Ti substrates by the application of SPEEK coatings [45,46]. On the other hand, various techniques have been applied with silver as the protagonist: thin films of Ag-SiO 2 nanocomposites of the sol gel type, materials of Ag / TiO 2 and AgNPs composites embedded in porous matrices [47,48].…”
Section: Antibacterial Behaviormentioning
confidence: 99%
“…In previous works, authors have already evaluated the bacterial behavior of porous Ti substrates with different proportions and sizes of pores [4], revealing a greater bacterial adhesion and proliferation in those samples with bigger pore size distribution. Similarly, they investigated a novel methodology to confer antimicrobial character to these Ti substrates by the application of SPEEK coatings [45,46]. On the other hand, various techniques have been applied with silver as the protagonist: thin films of Ag-SiO 2 nanocomposites of the sol gel type, materials of Ag / TiO 2 and AgNPs composites embedded in porous matrices [47,48].…”
Section: Antibacterial Behaviormentioning
confidence: 99%
“…The content, size, and morphology of the pores are responsible for the tribo-mechanical behavior (stiffness, hardness, mechanical strength, wear resistance, and scratch resistance) and corrosion resistance of porous titanium samples. On the other hand, it has been reported in the literature that pores with an adequate size allow the growth of bone tissue into the implant, as well as infiltration and adhesion of coatings [17,18], while optimal surface roughness facilitates the adhesion of osteoblasts (potential improvement of osseointegration). In this context, porous titanium parts manufactured with 50% vol.…”
Section: Electrical Impedance Spectroscopy and Porosity Characterizationmentioning
confidence: 99%
“…In this section, a first detailed study on the morphology of the coatings is presented to evaluate the quality of the biopolymeric coatings on the porous substrates’ surfaces. (Details on the characterization of the porous substrates can be found in references [ 12 , 13 , 14 , 15 ]). Next, the influence of the pore content of titanium substrates and the chemical composition of the chitosan-based nanocomposite coatings on the corrosion resistance and cellular behavior (adhesion and proliferation of osteoblasts) are discussed.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, although it has been previously reported that the walls of the pores obtained using the SH technique present a micro-scale roughness pattern that favors osteoblast adhesion [ 5 , 11 ], it is still necessary to implement superficial modification routes of the implants that improve osseointegration with the surrounding bone tissue. A detailed characterization of the porous substrates surfaces and the influence of the different porosities in balancing the mechanical properties and how it affects bacterial behavior can be found in our previous works [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%